2020
DOI: 10.1111/apa.15672
|View full text |Cite
|
Sign up to set email alerts
|

Interviews with patients aged 6–17 years provide valuable insights for physicians who need to deliver an epilepsy diagnosis

Abstract: Aim Meeting children's needs when communicating an epilepsy diagnosis can have a large impact on their treatment. We investigated children's experiences and wishes concerning their first conversation about epilepsy. Methods This prospective study was performed in the neuropaediatric departments of two German university hospitals from 2 October 2018 to 12 April 2019. The semi‐structured interview contained open questions, and multiple answers were allowed. Results We interviewed 101 patients (57 male) aged 6–17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In individual interviews, the interviewer questions the pediatric patient about the experienced facts and perception of the topic of the research question [ 36 ]. In the included studies, pediatric patients were for example interviewed about their expectations regarding the quality of the nursing care [ 37 ] or about their experiences and wishes with regard to their first conversation about epilepsy with their clinician [ 38 ]. The interviews were conducted in different ways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In individual interviews, the interviewer questions the pediatric patient about the experienced facts and perception of the topic of the research question [ 36 ]. In the included studies, pediatric patients were for example interviewed about their expectations regarding the quality of the nursing care [ 37 ] or about their experiences and wishes with regard to their first conversation about epilepsy with their clinician [ 38 ]. The interviews were conducted in different ways.…”
Section: Resultsmentioning
confidence: 99%
“…The interviews were conducted in different ways. Almost all studies used a semi-structured interview [ 38 40 ], but a few studies conducted an unstructured interview [ 41 ]. Furthermore, the majority of interviews were held face-to-face in the clinical setting [ 37 39 ] or at the patients’ home [ 40 ], and a few interviews were conducted by telephone [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“… 18 One study found that rates of perceived stigma were higher among YWE compared to youth with other chronic illnesses. 22 Of the 5 studies 22 , 24 , 26 , 28 , 32 that discussed the prevalence of YWE self-disclosure, rates ranged from 18% 22 to 65%. 26 …”
Section: Resultsmentioning
confidence: 99%
“…18 One study found that rates of perceived stigma were higher among YWE compared to youth with other chronic illnesses. 22 Of the 5 studies 22,24,26,28,32 that discussed the prevalence of YWE self-disclosure, rates ranged from 18% 22 to 65%. 26 Regarding disclosure patterns, across studies YWE endorsed some level of concealment and disclosure, and often engaged in different disclosure behaviors depending on circumstances.…”
mentioning
confidence: 99%
“…Thus, it is important that physicians take the parents' and patients' concerns seriously and provide advice to alleviate those concerns, offer support and give further explanations, e.g., on the importance of regular drug intake [9,10,26]. In addition, children and adolescents with chronic conditions desire to be actively involved in physicians' counseling [9,26,27]. Those measures also could contribute to increase patients' adherence [28][29][30].…”
Section: Communication On Adrsmentioning
confidence: 99%